Iguatemi: creating opportunities for international luxury brands in Brazil - Fardilha, Marta Sofia Marques de Sá (2014)
The Brazilian luxury goods market has been registering substantial growth with many international brands establishing presence in the country. When entering the market, the perfect location seems for most of them to be found in Iguatemi Group’s Shopping Malls. This research focuses the topic of Luxury Market and Retail, in the form of a case study on Iguatemi Group, which tries to understand How is Iguatemi Group creating opportunities for International Luxury Brands in Brazil? To understand the context of the case, the text explores the Brazilian market evolution, its attraction factors and challenges, the location choice methodology used by international luxury brands, and finally, how is the Iguatemi Group creating opportunities for these brands in Brazil. For doing so, a multiple-methods approach was followed so to achieve a non-biased result. In-depth interviews were conducted with Iguatemi’s managers, international luxury brands’ managers and experts in luxury market and retail; non-participant observation was held, and documentation was examined. The research found that the entry of International Luxury Brands in Brazil started about 20 years ago, mainly explained by the positive structural economic reforms Brazil experienced in this period. 60% of the studied brands chose São Paulo’s Iguatemi malls as first location, in particular Iguatemi São Paulo and JK Iguatemi. The preference over these locations relies mainly on the reputation of the Iguatemi brand and on its positioning in the market which seems to be aligned to that of these brands. From its side, Iguatemi has started actively gathering international luxury brands into the market since 15 years ago, and has intensified its action by creating iRetail, an internal company to the group representing some international luxury brands in Brazil, which have, thus, exclusive locations in its malls. The role of Iguatemi, hence, goes beyond that of a real estate company, by approaching the market with a 360° strategy. These findings contribute for academic purposes, in the extent to which they propose a so far rather unexplored topic, and for managerial purposes by describing a best practice in the shopping center sector. However, the study does not mean to be generalized. Consumers’ perspectives on Iguatemi Group were not addressed; rather, the research took a business to business approach.